(untitled) (South East Asia Journal of Public Health, 2017)
Human Immune Deficiency Virus (HIV) and Acquired immune Deficiency Syndromes (AIDS) continues to be a major burden of morbidity and mortality among the population. Injecting drug users (IDUs) are at high risk of contracting the disease. The study was conducted to assess the level of knowledge of HIV/AIDS and the influence of different socio-demographic factors among IDUs in Dhaka city, Bangladesh. A descriptive type of cross-sectional study was conducted. A total of 200 injecting drug users were selected purposively. A semi-structured questionnaire was used for collecting socio-demographic information of the respondents and their knowledge regarding HIV/AIDS. The level of knowledge was categorized into two: poor (<Mean – 1 SD) and good (≥Mean + 1 SD). The χ2 test was used for finding the association between socio-demographic factors and level of knowledge about HIV/AIDS. Forty-eight percent of the respondents were aged 18-26 years, and 33% were educated up to secondary level. About 47% had an income of Taka 4500-5500. Of the respondents, 41% and 47% were aware of HIV/AIDS and their preventive measures respectively. Age and education of the respondents were significantly (p<0.05) associated with level of knowledge of HIV/AIDS among IDUs. Functional and productive educational campaigns to educate people regarding the health consequences of HIV/AIDS are strongly suggested for creating awareness through disseminating knowledge among IDUs in Bangladesh particularly for the age group with a low level of knowledge and limited access to HIV/AIDS educational intervention programs. South East Asia Journal of Public Health Vol.7(1) 2017: 42-47